How do migrants choose their destination country?: an analysis of institutional determinants - Wido Geis; Silke Uebelmesser; Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2008)
For a long time, migration has been subject to intensive economic research. Nevertheless, empirical evidence regarding the determinants of migration still appears to be incomplete. In this paper, we analyze the effects of socio-economic and institutional determinants, especially labor-market institutions, on migrants' choices. Based on a large data set constructed from micro-data for France, Germany, the UK and the US, we study their decisions to migrate to one of the four countries using a Multinomial Choice framework. Our estimates confirm a number of conventional results such as positive effects of wages and immigrant networks and negative effects of unemployment rates. In addition, we find that employment protection, union coverage and unemployment benefits have positive effects on migration. Also good education and health systems tend to attract migrants, while generous pension systems may deter them. Based on separate estimations for high- and low-skilled migrants, there is evidence that the effects of labor-market institutions differ across skill groups.
Keywords: A00; J21; J31; J61; 330; Migration; labour-market institutions; micro-data; multinomial choice; Migranten; Entscheidung; Arbeitsmarktflexibilisierung; Lohn; Institutionelle Infrastruktur; Frankreich; Deutschland; Großbritannien; USA